1998
DOI: 10.1002/(sici)1521-3927(19980601)19:6<287::aid-marc287>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Sphere, honeycomb, regularly spaced droplet and fiber structures of polyion complexes of chitosan and gellan

Abstract: SUMMARY Different characteristic surface structures such as true and hemi spheres, honeycomb, regularly spaced droplets and fibers are created by electrostatic polysaccharide interaction between chitosan and gellan gum via polyion complex formation. Spherical droplet capsules of varying diameters form in solution. Strong fibers can be spun by gravity and by wet spinning in ethanol. These fibers possess a counter ion pairing structure, and exhibit a 'nervatiodveining' pattern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(31 citation statements)
references
References 0 publications
1
30
0
Order By: Relevance
“…This leads us to suggest, in accordance with most previous works, that at the interface of the two components forms a load-bearing strong skin that prevents diffusion of the polycation deep into the filament, resulting in a core-shell strucutre. 42,48,[57][58][59][60] The majority solid component was interpreted to be TOCN based on the color of the wet filament (see Figure 1c) when using dyed TOCN dispersion (blue) and polycation solution (pink, PDADMAC).…”
Section: Resultsmentioning
confidence: 99%
“…This leads us to suggest, in accordance with most previous works, that at the interface of the two components forms a load-bearing strong skin that prevents diffusion of the polycation deep into the filament, resulting in a core-shell strucutre. 42,48,[57][58][59][60] The majority solid component was interpreted to be TOCN based on the color of the wet filament (see Figure 1c) when using dyed TOCN dispersion (blue) and polycation solution (pink, PDADMAC).…”
Section: Resultsmentioning
confidence: 99%
“…Up to date, a limited number of CH-GG polyelectrolyte complexes have been reported as the focus has been on the development of capsules and fibers [161][162][163][164][165][166][167] . For example, Yamamoto and co-workers studied the characteristic structures of the interface between CH-GG due to charge overcompensation on the formation of fibers and capsule 162 .…”
Section: Types Of Wound Dressings Available On the Marketmentioning
confidence: 99%
“…This interface reaction could form a hemisphere, honeycomb shape or spaced droplets of polyelectrolyte complex. While the interface can be pulled out to form fibres, as reported by Amaike and co-workers 167 . Another study by Fujii et al 166 reported the encapsulation of alkaline phosphatase (ALP) by utilizing the polyelectrolyte complex technique of CH-GG as shown in Figure 1.5.…”
Section: Types Of Wound Dressings Available On the Marketmentioning
confidence: 99%
“…Oliveria et al demonstrated the formation of GG fibers through spinning alkaline GG solutions into a bath containing ascorbic acid (vitamin C) 126 . Several authors have also reported the formation of poly-ion complex fibers, whereby the polyanionic GG is spun alongside poly-cationic materials 139 . For example, Granero et al reports that GG fibers spun into a bath containing chitosan (and vice versa) generating complex fibers with enhanced mechanical properties 140 .…”
Section: Wet-spinningmentioning
confidence: 99%